If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(m) = 25(m) + 22 Reorder the terms: 9m = 22 + 25m Solving 9m = 22 + 25m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-25m' to each side of the equation. 9m + -25m = 22 + 25m + -25m Combine like terms: 9m + -25m = -16m -16m = 22 + 25m + -25m Combine like terms: 25m + -25m = 0 -16m = 22 + 0 -16m = 22 Divide each side by '-16'. m = -1.375 Simplifying m = -1.375
| 6m+14m=-16 | | 6b^2=-18b | | 21=2p-9 | | 40+3x+20-5x=30 | | G+2g+6=6g-21 | | 20x-27=73 | | 5(z)+8=4(z)+20 | | 1.3x+3=-1 | | -6x+9y=84 | | 2w-21.5=9 | | 2x-3y=-28 | | 40-4x=2-10 | | -24y^3-64y^2=0 | | (Y^2+3)(y^2-12)=0 | | 7(x-2)=4(x+5) | | 7x-28=6x-1 | | 3(X+4)+7X=4 | | 8+3b=2(9-b) | | 2f+700=-74 | | -10p+9p=13 | | (x-10)(x+2)= | | k(k-1)-30=0 | | 20+18k=956 | | (7y-10y)-11+3=7 | | 174=2+2x | | 4x-9x=60 | | sinx=0.26 | | D+(-1)=9 | | 46=14+8g | | -8b+5=-7b-5 | | 7k-5=40 | | -5(5y-9)-y=-3(y-4) |